小尺寸曲面构件全局缺陷精细定量识别方法 (2023)
本发明公开了小尺寸曲面构件全局缺陷精细定量识别方法，包括：利用透视变换模型对图像进行拼接，得到完整的红外重构拼接图像，将图像划分为基准图像部分、配准图像部分以及重叠区域部分；对红外重构拼接图像进行缺陷特征区域提取，得到缺陷特征区域；根据缺陷特征区域所处不同位置设计不同的坐标转换算法，获得像素点对应的瞬态热响应曲线，使用欧式距离或动态时间归整算法对缺陷热扩散区域像素点进行统计，进而得到缺陷特征区域对应的像素点个数，完成缺陷定量识别。本发明提高了图像拼接精度，减小了拼接误差，解决了重叠区域由于透视变换可能使缺陷形态发生畸变导致的重叠部分提取的部分缺陷的像素点个数的不准确问题。 The invention discloses a fine quantitative recognition method for global defects of a small-size curved surface component, which comprises the following steps of: splicing images by using a perspective transformation model to obtain a complete infrared reconstruction spliced image, and dividing the image into a reference image part, a registration image part and an overlapping region part; performing defect feature region extraction on the infrared reconstruction spliced image to obtain a defect feature region; and designing different coordinate conversion algorithms according to different positions of the defect feature region, obtaining transient thermal response curves corresponding to pixel points, and counting the pixe